Study of Advective Energy Transport in the Inflow and Outflow of Super-Eddington Accretion Flows - Cheng-Liang Jiao (The Astrophysical Journal, 2023)
Photon trapping is believed to be an important mechanism in super-Eddington accretion, which greatly reduces the radiative efficiency as photons are swallowed by the central black hole before they can escape from the accretion flow. This effect is interpreted as the radial advection of energy in one-dimensional height-integrated models, such as the slim-disk model. However, when multidimensional effects are considered, the conventional understanding may no longer hold. In this paper, we study the advective energy transport in super-Eddington accretion based on a new two-dimensional inflow–outflow solution with radial self-similarity, in which the advective factor is calculated self-consistently by incorporating the calculation of radiative flux instead of being set as an input parameter. We found that radial advection is actually a heating mechanism in the inflow due to compression, and the energy balance in the inflow is maintained by cooling via radiation and vertical ( θ -direction) advection, which transports entropy upward to be radiated closer to the surface or carried away by the outflow. As a result, fewer photons are advected inward, and more photons are released from the surface, so that the mean advective factor is smaller and the emergent flux is higher than the fluxes predicted by the slim-disk model. The radiative efficiency of super-Eddington accretion thus should be higher than that of the slim-disk model, which agrees with the results of some recent numerical simulations.